Konsep Urin Menurut Ibnu Sina: Kajian atas Kitab al-Qanuun fith-Thibb - Wahidi, Wahidi; Sopari, Onang; Wahidi (Jurnal Pendidikan Islam, 2015)
This article discusses the concept of urine according to Ibn Sina in his book al-Qanuunfith-Tibb and its relevance to the modern concept of urine formation at this time. Theconcept of urine formation, according to Ibn Sina is the cooperation process betweenthe liver, (liver), ureter (masaliku al-maiyyah / urinary pessages), kidney (Killi), sweatglands in the skin (‘uruq), gall (sofrowyyu) and bladder urinary. In retaltion with theconcept of urine, Ibn Sina did not mention in detail the tasks and functions of eachorgan that plays a role in the process of urine formation. Meanwhile the modern urineconcept by modern biologists have described up to the molecular level. The relevanceof Ibn Sina’s concept to the modern concept of urine formation, is that in Ibn Sina’sera the concept of urine formation had already at the level of organ and as bases offurther concept development through the molecular level. The modern biology concepthas happened division of the functions of each organ clearly, while the concept of IbnSina, organ is a unified and not specialized yet.